Carbon, nitrogen and phosphorus mineralization in two soils amended with distillery yeast - Rezende, L. A.; Assis, L. C.; Nahas, E. N. (Elsevier B.V., 2004)
The possibility of using yeast from alcohol distilleries as a source of nutrients in soil was investigated. The following treatments were used: no fertilization (control), 0.5% (w/w) yeast, 1% (w/w) yeast, and NPK. The decomposition of yeast was monitored for 90 days in two soils. The CO, production and the microbial biomass were increased by art average of 1- to 3-fold by yeast incorporation compared to control. Protease activity also was enhanced 3- to 8-fold in the soils supplemented with yeast compared to control. The phosphatase activities were higher than control only during the first days. While nitrate contents increased in all treatments compared to control, available P only increased in the soils amended with 1%, yeast or NPK by 45-119% and 309-489%, respectively. These results indicate that there exists an excellent potential for the use of yeast in the soil as a source of nitrate and available P for plant nutrition. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: distillery yeast; soil amendment; CO2 production; biomass-C; biomass-N; Protease; phosphatase; nitrate; available p